Deficiência de ferro como indicador de risco para cárie de estabelecimento precoce severa em crianças de 24 a 36 meses - Gomes, Isabella Azevedo (2009)
The aim was evaluate the association between iron deficiency and severe early childhood caries in children between 24 and 36 months; rising hematological indicators that can be related to early establishment of the disease. At intraoral exam the caries index (def) praised by WHO, and the presence of active white spots (AWP) were evaluated. All the children were submitted to a bloody collection, being the samples frozen and sent to processing at Hemomar Analysis Laboratory (São Luís, Maranhão, Brazil), for the evaluation of hemoglobin, ferritin and serumal iron levels. The obtained information was consolidated in data bank of STATA 9.0 program. The Poisson regression model was applied to the association between dependent variables (def and AWP) and others, being the prevalence ratio and confidence interval (IC 95%). It was certified that the higher the number of caries cavities in children, the lower are the hemoglobin levels in serum. About caries activity (AWP), it was observed that the higher the number of initial lesions, the lower is the levels in serum of hemoglobin, ferritin and serumal iron. The data show that the levels in serum of the marked variables of iron deficiency anemia are lower when the number of caries lesions in children with severe early childhood caries is higher.